Linking the African Past and Present: Corrective Representation of Women in Aminatta Forna’s Ancestor Stones - Nataša V. Ninčetović (Društvene i Humanističke Studije, 2025)
Starting from the observation that African women are often underrepresented and misrepresented in both African male literature and Western fiction, this paper offers evidence that Aminatta Forna’s Ancestor Stones (2006) aims at inscribing African women into history by focusing on their experiences. Forna’s debut novel not only challenges gender stereotyping but also deals with themes of women’s position and marriage in past and present West African society. A close reading of the novel suggests that whereas the female principle was valued in Africa’s pre-colonial era, in colonial Africa women were respected solely for their reproductive role. Precisely for this reason, women opted for marriage. The novel indicates that while marriage did mean security in the past, this is not the case in the present. The implication is that the changing historical and cultural circumstances necessitate a redefinition of the institution of marriage as a union based on equality and appreciation. Ancestor Stones acknowledges that there are greater opportunities for African women regarding access to education and occupations. However, this progress is overshadowed by the persistence of gender stereotypes and prejudice. Drawing on Nnaemeka’s collection of essays The Politics of (Mo)Othering: Womanhood, Identity and Resistance in African Literature, the article argues that women, despite being oppressed, can and should fight against this state of affairs. By highlighting the examples of women who rebelled against inequality and humiliation, the novel points to the direction of action toward the desired liberation and empowerment of women.